Diagnostic Approach and Management of Sjogren's Syndrome - Elsy Pramitha Sari; Raveinal (PROFESSIONAL HEALTH JOURNAL, 2026)
Sjogren’s syndrome (SS) is a chronic autoimmune disorder characterized by sicca symptoms, particularly xerostomia, resulting from salivary gland dysfunction. Accurate assessment of glandular function and systemic disease activity is essential, as subjective complaints often do not correlate with objective clinical measurements. This study aimed to evaluate diagnostic and therapeutic approaches in patients with primary Sjogren’s syndrome based on objective salivary gland function assessment and standardized measurement of systemic disease activity. Methods: This observational study included patients diagnosed with primary Sjogren’s syndrome. Subjective xerostomia was assessed using the Summated Xerostomia Index–Indonesian version (SXI-ID), while objective evaluation was performed using the unstimulated whole salivary flow rate and the Clinical Oral Dryness Score (CODS). Systemic disease activity was measured using the EULAR Sjogren’s Syndrome Disease Activity Index (ESSDAI). All assessments were conducted prior to treatment initiation and periodically during follow-up. Non-autoimmune etiologies were excluded through comprehensive history taking, physical examination, and relevant investigations. A discrepancy was observed between subjective xerostomia complaints and objective salivary function measurements. ESSDAI scoring demonstrated variability in systemic disease activity, categorized as low, moderate, and high. A multidisciplinary approach contributed to accurate diagnosis and evaluation of organ involvement. Therapeutic decision-making in Sjogren’s syndrome should be guided by objective salivary gland function assessment and standardized systemic activity indices such as ESSDAI, rather than relying solely on subjective patient-reported symptoms. The integration of subjective and objective evaluations through periodic monitoring may enhance therapeutic precision and improve long-term disease management outcomes in patients with Sjogren’s syndrome.